Microwave Assisted Synthesis of MoS2/PANI/ZnO Nanocomposites as a Working Electrode for Energy Storage Applications - Balavijayalakshmi, J.; Krithika, S. (Asian Journal of Chemistry, 2021)
Transition metal dichalcogenide and polyaniline doped zinc oxide nanocomposites influence the transition probabilities and electronic structure. In present study, the various concentrations of MoS2/PANI/ZnO nanocomposites are synthesized by microwave assisted method. These nanocomposites are characterized by using XRD, FESEM, HRTEM and FT-IR. The XRD results revealed an average crystallite size of synthesized nanocomposites, which was found to be 19-24 nm. The electrochemical properties of the nanocomposites are studied through the CV, EIS and GCD for the application of supercapacitor as an active electrode material. The MoS2/PANI/ZnO nanocomposites exhibited a specific capacitance of 577 F g-1 and also retained 90% of its initial specific capacitance even after 5000 cycles. Hence MoS2/PANI/ZnO nanocomposites have potential application for energy storage applications.